The Implementation of Quizizz in Learning at SDN 08 Sui Ruk Bengkayang - Nasution, Helfi; Sujaini, Herry; Septiriana, Rina; Muthahari, Morteza; Hafidh, Khairul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2023)
The development of Information and Computer Technology (ICT) has had a broad impact on various sectors of life, including the education sector and ICT mastery. Through formal education, students are equipped with insight from an early age which becomes the basis for continuous learning and developing problem-solving skills. However, in Bengkayang District, West Kalimantan, the ICT education program has not yet reached students in several rural schools, including SDN 08 Sungai Ruk, where students are not familiar with computers both in terms of hardware and software. In addition, the COVID-19 pandemic has had a significant impact on education. Since March 16 2020 in Indonesia, students have been studying from home through an online system to prevent the spread of the virus. Nonetheless, the government continues to encourage teaching and learning activities even though remotely. Based on these problems, Quizizz is implemented for students of SDN 08 Sungai Ruk so that elementary school students have knowledge and skills in operating computers both in terms of hardware and software, and increase learning motivation. This implementation provides an introduction to computer introduction material regarding computer basics such as computer components and their functions. Followed by a Fun Game that aims to break the ice. And finally an interactive quiz was held using the Quizizz platform which was based on the material previously presented.